Genetic variation in the neuropeptide Y gene promoter is associated with increased risk of tobacco smoking - Mutschler, Jochen; Goltz, Christoph von der; Dinter, Christina; Kiefer, Falk (European addiction research, 2012)
Background: Neuropeptide Y (NPY) is a strong candidate gene regarding the pathophysiology of tobacco dependence. It has been associated with various addictive and psychiatric disorders, and closely interacts with the brain reward system. The aim of the present study was to test for association between a functional genetic variant in the NP-Y promoter gene (SNP rs16147) and tobacco smoking. Methods: In a population-based case-control multicenter study designed for tobacco addiction research, a total of 550 Caucasian current smokers, and 544 never-smokers were genotyped for SNP rs16147 and behaviorally characterized with the State-Trait Anxiety Inventory (STAI). Results: Subjects with TT genotype of the SNP rs16147 were significantly more frequently smokers than never-smokers (p = 0.046). In addition, TT genotype exhibited increased state anxiety scores compared to carriers of the C allele (p = 0.037). Conclusions: Our results provide evidence for an involvement of the functionally relevant SNP rs16147 in the pathophysiology of tobacco dependence. Further studies are needed to confirm our findings.